(untitled) (Journal of Applied Membrane Science & Technology, 2022)
Tofu whey, liquid waste of tofu processing, contains valuable components including protein, mono- and di-saccharide (glucose, fructose, sucrose, MDS) and soy oligosaccharide (stachyose, raffinose, SOS). Recovery of these components, therefore, is essential regarding sustainable food processing approach. Ultrafiltration (UF) has been successfully used for concentration of tofu whey protein. In this study, nanofiltration was employed to harvest and purify SOS from tofu whey UF-permeate. NF-membrane selection, hydrolysis of tofu whey UF-permeate and NF of pre-hydrolysis of tofu whey UF- permeate were performed to achieve the best condition for purification. It was found that the membrane, NF-DK-2540 was superior than that of NF-DL-2540 with the retention rate of stachyose (94%), raffinose (87%), sucrose (65%), glucose (7.8%) and fructose (4.3%). These results indicated that NF could harvest SOS and remove monosaccharide with acceptable retention. However, its sucrose retention was considerably high. Therefore, an enzymatic hydrolysis of UF-permeate was employed to convert sucrose to glucose and fructose. The results indicated that the use of NF combined with enzymatic hydrolysis could significantly remove MDS from tofu whey UF-permeate and consequently increasing the purity of SOS.